Memorial Boxes and Guarded Interiors : Edith Wharton and Material Culture - Totten, Gary (Book collections on Project MUSE., 2007)
American writer Edith Wharton (1862-1937) once wrote in Harper's that she wanted to "penetrate ... the carefully guarded interior[s]" of her past memories and fashion them "into a little memorial like the boxes formed of exotic shells which sailors used to fabricate between voyages." For Totten (English, North Dakota State U.) this statement is a striking reminder of the connections between material objects and cultural meanings in Wharton's life and work. He presents 11 essays that explore these connections in a variety of ways. Topics include critical linkages of Wharton to materiality as a means to keep her outside the canonical, resistance to commodification in The House of Mirth, the creation of the disposable object and Wharton's characters' fears of their disposability, Wharton's ideas about the use of museum space in The Age of Innocence, and the effect of technology on domestic space in The Fruit of the Tree